Correlation of Antioxidant Properties Between Immature and Mature Okra (Abelmoschus Esculentus) Fruits - Nazri, Miza Badriah; Azlan, Azrina; Sultana, Sharmin; Yahya, Rozita (Talenta Publisher, 2024)
This study aimed to assess and compare the antioxidant activity and content (total flavonoid levels and total phenolic) of mature and immature okra. The antioxidant activity of okra fruits was assayed using four methods, namely: Aluminium Chloride Colorimetric assay, Folin-Ciocalteu assay, 1, 1-diphenyl-2-picrylhydrazyl (DPPH), and Reducing Antioxidant Power assay (FRAP) assays. The immature, mature, and very mature okra samples (less than 8 days, 10-15 days, and more than 20 days, respectively) were extracted using two different solvents (65% ethanol and water). The sample that was extracted with mature ethanol had the highest Total Phenolic Content (TPC) at 21.564 ± 1.635 mg GAE/g, while the sample that was extracted with extremely mature ethanol had the highest TFC at 54.391 ± 8.224 mg QE/g. The mature 65% ethanolic extracted sample showed the lowest IC50 value of DPPH scavenging activity (0.920± 0.096 mg/ml), and the mature ethanol extracted sample had the highest FRAP value (232.018± 5.337 μmol Fe2+/g). These studies showed that ethanolic extracts of mature Abelmoschus esculentus had higher antioxidant content and activity than okra water extracts. Based on the DPPH Radical Scavenging Assay revealed favourable associations between TPC (r = 0.860), TFC (r = 0.742), and antioxidant activity as evaluated by FRAP, demonstrating that both phenolics and flavonoids contributed to the extract’s antioxidant properties. Both TPC and TFC showed negative correlations with IC50 values (r = -0.766, r = -0.650, respectively). In conclusion, the mature okra fruits extracted with 65% ethanol give higher antioxidant content than the water extracts of okra fruits and potentially be used as a source of antioxidants rather than be discarded.